PERFORMANCE ANALYSIS OF WORKING FLUIDS ON ORGANIC RANKIE CYCLE (ORC) MODEL WITH BIOMASS ENERGY AS A HEAT SOURCES - Lilis Sucahyo; Muhamad Yulianto; Edy Hartulistiyoso; Irham Faza (The University of Lampung, 2019)
Organic Rankine Cycle (ORC) is an electricity power technology particularly suitable for medium-low temperature heat sources and/or for small available termal power. This paper presents the simulation and performance analysis of working fluids R-134a, R-414B, R-404A and R-407C on ORC with biomass energy as a heat source. Simulation of the ORC system using Cycle Tempo software. The property of working fluids is obtained by using Reference Fluid Properties (Refprop). The best result performance of ORC was shown by working fluid R-404A with thermal efficiency 7.54 % and electric power output ranges between 0.075 kW. This condition operated on turbine inlet temperature at 60 oC, difference turbine working temperature of 15 oC, condensing temperature 25 oC and water boiler mass flow rate 3 lpm.